2012
DOI: 10.1007/s10803-012-1723-5
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone Dosing in Children and Adolescents with Autistic Disorder: A Double-Blind, Placebo-Controlled Study

Abstract: Efficacy and safety of 2 risperidone doses were evaluated in children and adolescents with autism. Patients (N = 96; 5-17 years), received risperidone (low-dose: 0.125 mg/day [20 to <45 kg], 0.175 mg/day [>45 kg] or high-dose: 1.25 mg/day [20 to <45 kg], 1.75 mg/day [>45 kg]) or placebo. Mean baseline (range 27-29) to endpoint change in Aberrant Behavior Checklist-Irritability (primary endpoint) was significantly greater in the high-dose-(-12.4 [6.5]; p < 0.001), but not low-dose (-7.4 [8.1]; p = 0.164) group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 27 publications
2
100
1
Order By: Relevance
“…From the 10 trials comparing risperidone to placebo , mean weight gain with risperidone was 2.04 kg (Table ). The majority were short‐term studies (3–8 weeks), although in two studies the trial duration was 6 months .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 10 trials comparing risperidone to placebo , mean weight gain with risperidone was 2.04 kg (Table ). The majority were short‐term studies (3–8 weeks), although in two studies the trial duration was 6 months .…”
Section: Resultsmentioning
confidence: 99%
“…Where studies compared more than one dose of risperidone to placebo, only the highest dose is shown in the table. Three studies reported a significant weight gain with risperidone and six showed a non‐significant trend for weight gain with the medication . Several other studies did not meet the specific inclusion criteria, as they were not randomized controlled trials, but they assist in forming an impression of risperidone‐related weight gain and a short discussion therefore follows.…”
Section: Resultsmentioning
confidence: 99%
“…However, significant side-effects are associated with risperidone use, including weight gain from increased appetite, drowsiness, and increased levels of the hormone prolactin, which is produced by the pituitary gland and which can have a feminizing effect on both females and males [109]. The frequency of side-effects appears to be dose-related [110], and while weight gain is common, somnolence more significantly influences the discontinuation of treatment [111]. In 2009, following evaluation of short-term efficacy and safety, the FDA also approved aripiprazole, a third-generation atypical antipsychotic, for the treatment of irritability associated with ASD in children and adolescents [112, 113].…”
Section: Treatment Options In Asdmentioning
confidence: 99%
“…Nonetheless, it is noteworthy that risperidone is approved for use in children with autism, a disorder that is characterized by impaired social interaction. Some clinical studies (Jesner, Aref-Adib, & Coren, 2007; Scahill et al, 2013), but not all (Kent et al, 2013), have shown that risperidone alleviates social withdrawal in autism. From a translational point of view, our results suggest that the clinical impact of risperidone on developmental social behavior be monitored not only during the peak of active treatment but also throughout an entire dosing period.…”
Section: 0 Discussionmentioning
confidence: 99%